2011
DOI: 10.1530/jme-11-0046
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of estradiol and progesterone in insulin resistance through constitutive androstane receptor

Abstract: Normal pregnancy is characterized by insulin resistance, which contributes to the development of gestational diabetes mellitus and preeclampsia by incompletely understood mechanisms. The constitutive androstane receptor (CAR) may participate in insulin resistance in pregnancy, and sex steroids, estradiol (E 2 ) and progesterone, may also be involved. We applied glucose and insulin tolerance tests and measured the expression of gluconeogenic and lipogenic genes in the livers of oophorectomized mice treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Recent in vivo studies have demonstrated that the activation of CAR improves insulin sensitivity via glucose and lipid metabolic pathways; moreover, CAR null mice had spontaneous insulin insensitivity that could be relieved by CAR ligand (7,8), suggesting that CAR plays some roles in insulin resistance. We have recently demonstrated that the activation of CAR-mediated signaling can ameliorate insulin resistance under relatively high concentrations of estradiol and progesterone, which are compatible with pregnancy via decreased activities of transcription factors in gluconeogenesis in combination with CAR (19). We also observed that HFD-induced obese pregnant mice had high blood pressure and proteinuria, whereas treatment with CAR ligands ameliorated these signs (20).…”
mentioning
confidence: 79%
“…Recent in vivo studies have demonstrated that the activation of CAR improves insulin sensitivity via glucose and lipid metabolic pathways; moreover, CAR null mice had spontaneous insulin insensitivity that could be relieved by CAR ligand (7,8), suggesting that CAR plays some roles in insulin resistance. We have recently demonstrated that the activation of CAR-mediated signaling can ameliorate insulin resistance under relatively high concentrations of estradiol and progesterone, which are compatible with pregnancy via decreased activities of transcription factors in gluconeogenesis in combination with CAR (19). We also observed that HFD-induced obese pregnant mice had high blood pressure and proteinuria, whereas treatment with CAR ligands ameliorated these signs (20).…”
mentioning
confidence: 79%
“…The main limitation of the present study is that we only had data on crude surrogate measures of insulin sensitivity; however, this may tend to increase noise variations and bias the differences towards the null. In addition, we had no data on maternal oestriol and placental lactogen levels, which are associated with the normal increase in insulin resistance in pregnancy [3,4], and have been reported (but not validated) to be higher in women bearing a female than in women bearing a male fetus [5,6]. Future studies may validate whether maternal oestriol and placental lactogen levels are elevated in pregnancies with a female fetus, and whether such elevations are correlated with higher insulin resistance in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of estrogens, which occur during pregnancy, are sufficient to activate CAR to induce CYP2B6 expression [68]. Estradiol and progesterone concentrations within this elevated physiological range during pregnancy may play a role in glucose tolerance and insulin resistance working through CAR [69]. Furthermore, CAR represses estrogen receptor (ER)-mediated transcriptional activation in cell-based transfection assays, and this action is proposed to occur by competition of CAR with ER for the existing coregulator pool, thus limiting availability for ER transactivation [70].…”
Section: Biological Significance Of Carmentioning
confidence: 99%